Epigenetic Manipulation of Psychiatric Behavioral Disorders Induced by Toxoplasma gondii - Yin, Kun; Xu, Chao; Zhao, Guihua; Xie, Huanhuan (Frontiers in Cellular and Infection Microbiology, 2022)
Toxoplasma gondii is known to have a complex life cycle and infect almost all kinds of warm-blooded animals around the world. The brain of the host could be persistently infected by cerebral cysts, and a variety of psychiatric disorders such as schizophrenia and suicide have been reported to be related with latent toxoplasmosis. The infected animals showed fear reduction and a tendency to be preyed upon. However, the mechanism of this “parasites manipulation” effects have not been elucidated. Here, we reviewed the recent infection prevalence of toxoplasmosis and the evidence of mental and behavioral disorders induced by T. gondii and discussed the related physiological basis including dopamine dysregulation and gamma-aminobutyric acid (GABA) pathway and the controversial opinion of the necessity for cerebral cysts existence. Based on the recent advances, we speculated that the neuroendocrine programs and neurotransmitter imbalance may play a key role in this process. Simultaneously, studies in the evaluation of the expression pattern of related genes, long noncoding RNAs (lncRNAs), and mRNAs of the host provides a new point for understanding the mechanism of neurotransmitter dysfunction induced by parasite manipulation. Therefore, we summarized the animal models, T. gondii strains, and behavioral tests used in the related epigenetic studies and the responsible epigenetic processes; pinpointed opportunities and challenges in future research including the causality evidence of human psychiatric disorders, the statistical analysis for rodent-infected host to be more vulnerable preyed upon; and identified responsible genes and drug targets through epigenetics.